The Role of Artificial Intelligence to Improve Workplace Satisfaction and Productivity: A Qualitative Case Study of Healthcare Workers in Indonesian Hospitals - Encep Sopandi; Loso Judijanto; Agustin Amborowati; Andi Subhan Amir; Mochammad Isa Anshori (Fundamental and Applied Management Journal, 2026)
This study investigates the function of AI in enhancing workplace satisfaction and productivity among healthcare workers while identifying organizational challenges related to Artificial Intelligence implementation in an Indonesian hospital. A qualitative case study was conducted at Hospital S, Malang City, Indonesia. Ten healthcare workers with direct experience using Artificial Intelligence-supported healthcare systems were selected through purposive sampling. Data was gathered using semi-structured interviews, observations, and looking at documents. Then, the data was studied using the Miles and Huberman method, which includes steps like simplifying the information, organizing it into patterns, and finally drawing conclusions. Drawing and verification. Artificial Intelligence improved workplace satisfaction by reducing administrative workloads, supporting professional development, enhancing work experiences, promoting transparent decision-making, and strengthening collaboration. Artificial Intelligence also increased workplace productivity through faster clinical decision-making, improved operational efficiency, automation of routine administrative tasks, reduced medical errors, effective human–technology collaboration, and improved healthcare service quality. Nevertheless, resistance to organizational change, concerns regarding workforce replacement, and the need for continuous technological training remained significant implementation challenges. Artificial Intelligence has considerable potential to improve both workplace satisfaction and productivity when supported by appropriate organizational strategies. Human-centered AI implementation, continuous digital competency development, and effective organizational support are essential to maximize the benefits of Artificial Intelligence adoption and promote sustainable improvements in healthcare services.